2014
DOI: 10.1136/bmjopen-2013-004081
|View full text |Cite
|
Sign up to set email alerts
|

Family planning and pregnancy issues for women with systemic inflammatory diseases: patient and physician perspectives

Abstract: ObjectivesTo identify family planning and pregnancy (FPP) issues for female patients of childbearing age living with a chronic inflammatory disease and to assess whether current clinical practice routinely provides adequate support to alleviate these concerns.SettingMultinational survey and an analysis of online patient activity.ParticipantsPremenopausal women (aged 20–45 years; N=969) were surveyed in the USA, the UK, Germany, France, Italy and Spain. Rheumatologists were surveyed in Germany (N=50), France (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 30 publications
2
50
0
2
Order By: Relevance
“…For example, in several studies, young women with rheumatic diseases reported that they rarely received contraceptive counseling, even when starting an antirheumatic drug with fetotoxic potential . A survey including rheumatologists indicated that only 32–56% of these physicians had recently discussed family planning with female patients . However, no prior studies to our knowledge have explored rheumatologists’ in‐depth perspectives regarding FPCC for young, female patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in several studies, young women with rheumatic diseases reported that they rarely received contraceptive counseling, even when starting an antirheumatic drug with fetotoxic potential . A survey including rheumatologists indicated that only 32–56% of these physicians had recently discussed family planning with female patients . However, no prior studies to our knowledge have explored rheumatologists’ in‐depth perspectives regarding FPCC for young, female patients.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of physicians treating women with systemic inflammatory diseases found that only 32 – 56% of physicians reported having talked about family planning and pregnancy with their female patients of reproductive age. (8) Most patients reported that their family planning and pregnancy concerns were not adequately addressed or settled during their appointments. (8) When discussion does occur patients often report inconsistency in the advice they receive from different providers.…”
Section: Introductionmentioning
confidence: 99%
“…(8) When discussion does occur patients often report inconsistency in the advice they receive from different providers. (8,9)…”
Section: Introductionmentioning
confidence: 99%
“…For women affected by chronic inflammatory diseases, such as rheumatoid arthritis (RA), axial spondyloarthritis (SpA), psoriatic arthritis (PsA), and Crohn's disease (CD), disease onset, diagnosis, and initiation of treatment increasingly overlap with peak reproductive age (1,2). For many of these patients, disease activity during pregnancy requires effective management to maintain maternal health and ensure optimal fetal outcomes.…”
mentioning
confidence: 99%